2017
DOI: 10.4309/jgi.v0i37.3994
|View full text |Cite
|
Sign up to set email alerts
|

The Modified Gambling Motivation Scale: Confirmatory Factor Analysis and Links With Problem Gambling

Abstract: The Gambling Motivation Scale (GMS), a scale based on self-determination theory, consists of seven motivations: to learn the game, to feel competent, to experience excitement, to socialize, to feel important, to win money, and to continue gambling aimlessly (Chantal, Vallerand, & Vallieres, 1994). The GMS has never been tested with confirmatory factor analysis to determine the appropriate structure of gambling motivation. In the present study, we developed the Modified Gambling Motivation Scale (MGMS) to impro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…The GMS is based on motivational theory and provides better insight into gambling motivation than other scales do (Shinaprayoon et al, 2017). The GMS examines seven intrinsic and extrinsic motivations: to learn the game, to feel competent, to experience excitement, to socialize, to feel important, to win money, and to continue gambling aimlessly (Chantal et al, 1994).…”
Section: Gambling Motivation Scale (Gms)mentioning
confidence: 99%
“…The GMS is based on motivational theory and provides better insight into gambling motivation than other scales do (Shinaprayoon et al, 2017). The GMS examines seven intrinsic and extrinsic motivations: to learn the game, to feel competent, to experience excitement, to socialize, to feel important, to win money, and to continue gambling aimlessly (Chantal et al, 1994).…”
Section: Gambling Motivation Scale (Gms)mentioning
confidence: 99%
“…A Scree-plot and assessment of the interpretability of the solution indicated that a single factor solution was the best one. The items were chosen in preference to the Gambling Motivations Scale (Shinaprayoon et al, 2017) or Gambling Effects Scale (Flack & Stevens, 2019) because we were interested in the perceived benefits or outcomes of gambling as opposed to what people might hope to gain from gambling (their motivation). Items included: Gambling makes me: feel happy; keeps my mind active; gets me out of the house and gives me something to do; is exciting for me; gets me out doing things with other people; makes my life more interesting; gives me something to look forward to, as well as "I would miss not being able to gamble if the activity was not available", "I would go out less if there were no gambling activities" and "I would feel unhappy or bored if I could not gamble".…”
Section: Benefits Of Gamblingmentioning
confidence: 99%
“…It is well-documented that people gamble in the hope of receiving benefits from gambling. Many of these motivations or expectations are captured by a range of motivational measures (Abarbanel, 2014;Flack & Stevens, 2019;Nower & Blaszczynski, 2010;Shinaprayoon, Carter, Goodie, 2017). Such motivations include the desire to win money, to relax or escape from problems, social motives, or a desire to apply skill or feel important.…”
Section: Introductionmentioning
confidence: 99%